Zirconia Strength Degradation Post Air-Abrasion of Veneering and Cementation Surfaces. (2022) - Butler, S.; Linke, B.; Moreira, N.C.F.; Nychka, J.A.
Abstract : Purpose/Aim: This study evaluated how the flexural strength of a zirconia-based ceramic (Y-TZP) was affected by air abrasion with 30 μm SiO on both zirconia surfaces: the cementation surface, and the veneering surface. Materials and Methods: Translucent Y-TZP ceramic bars, for four-point bend testing, were prepared and divided considering the compressive (surface treatment for cementation) and tensile surfaces (surface treatment for veneering). Sandblasting was performed or not for each compressive and tensile surfaces. The specimens from all experimental conditions were analysed by SEM. All specimens were tested in four-point bending. Data were statistically analysed using one-way ANOVA and Post Hoc tests (α= 0.05). A Weibull analysis was used to analyse the strength reliability. Results: According to the results of this investigation, the flexural strength was significantly affected by sandblasting on both surfaces: for veneering (P < 0.001) and for cementation (P < 0.001). Conclusions: Sandblasting the veneering surface, to improve bonding of the veneer to Y-TZP, negatively impacted strength reliability. Sandblasting the cementation surface decreased the flexural strength while increasing the strength reliability.